Effect of Nb content on microstructure and properties of FeCoNi2CrMnV0.5Nbx high-entropy alloy coatings by laser cladding - Rui Zhang; Xiaoyan Gu; Haotian Gong; Xiaopeng Gu; Xiaohui Zhao (Journal of Materials Research and Technology, 2022)
By laser cladding, FeCoNi2CrMnV0.5Nbx high-entropy alloy (HEA) coatings with different content of Nb were fabricated on the ZG25MnNi cast steel in the current study. The microstructure evolution, microhardness, corrosion resistance and wear resistance of FeCoNi2CrMnV0.5Nbx HEA coatings were studied systematically. The results indicated that the HEA alloy coatings transformed into dendrite (DR) structure after adding the Nb element. The dendrite was FCC phase and the interdendritic (IR) eutectic structure was composed of the FCC phase and Laves phase. The wear resistance and microhardness of the HEA coatings increased gradually with the increase of Nb content. When the Nb content x was 1.2, the microhardness of the upper part of the coatings reached 631.1 HV, which was 4 times higher than that of the base metal, and the wear resistance was improved to about 14.2 times the substrate. With the increase of Nb content, the corrosion resistance of coatings first increased and then weakened. When the Nb content x was 0.8, FeCoNi2CrMnV0.5Nbx HEA coatings had the best corrosion resistance.